2021
DOI: 10.1002/aepp.13188
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and agricultural productivity in Burkina Faso

Abstract: In this paper, we examine the interplay between remittances and agricultural productivity in Burkina Faso. We estimate a Bayesian instrumental variables model using data from the 2014 Living Standards Measurement Study. We consider three measures of agricultural productivity: total production, total production per unit of land, and total production per unit of labor. Whatever the measure used, our results reveal a significant and negative association between remittances and agricultural productivity. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…The result for maize and cocoa is consistent with some existing studies in developing countries, which have found that the effect of receiving remittances as a nonlabor source of income could result in a state of dependency, thereby reducing the labor market participation of the recipient households and their production activities (see Lipton, 1980;Berker, 2011;Dedewanou and Kpekou Tossou, 2022). The negative relationship between remittances and agricultural productivity confirms similar results by Akudugu (2016) but insignificant relationship between remittances and productivity.…”
Section: Average Treatment Effectssupporting
confidence: 89%
See 4 more Smart Citations
“…The result for maize and cocoa is consistent with some existing studies in developing countries, which have found that the effect of receiving remittances as a nonlabor source of income could result in a state of dependency, thereby reducing the labor market participation of the recipient households and their production activities (see Lipton, 1980;Berker, 2011;Dedewanou and Kpekou Tossou, 2022). The negative relationship between remittances and agricultural productivity confirms similar results by Akudugu (2016) but insignificant relationship between remittances and productivity.…”
Section: Average Treatment Effectssupporting
confidence: 89%
“…Akpan et al (2014) examine the relationship at the macroeconomic level for Nigeria and find that in the short run remittances have a positive and significant effect on agricultural productivity, but this effect disappears in the long run. A recent study by Dedewanou and Kpekou Tossou (2022) on farming households in Burkina Faso also find that although remittances increase labor input there is a negative relationship between remittances and total agricultural productivity, confirming the findings of Zahonogo (2011). These findings are somewhat puzzling and create a need for further inquiry.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations